Research on the examination reform of the course of numerical analysis - Li, Aijuan; Zhou, Shixiang (IJRDO- Journal of Educational Research, 2019)
In this paper, we have carried out an examination reform of  the course of numerical analysis in the face of some problems. The process assessment of the course of numerical analysis has been added. By the examination reform of the course of numerical analysis, it is obvious that students' interest in learning numerical analysis has been increased, and their ability to solve practical problems by using numerical calculation methods has been improved.